Narrative Pointes Thoughts on George Balanchine's Prodigal Son - Goldner, Nancy (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Thoughts on Prodigal Son. PALABRAS CLAVE: Georges Balanchine, Prodigal Son, Diaghilev, Ballet Russes.